A Predictive Model for Cancer-Associated Thrombosis in Japanese Cancer Patients: Findings from the J-Khorana Registry - Shoji, Masaaki; Yamashita, Yugo; Ishii, Masanobu; Inoue, Hitoki; Kato, Hiroshi; Fujita, Shin; Matsui, Kazuhiro; Tajiri, Kazuko; Nameki, Mizuo; Muraoka, Nao; Nonaka, Akiko; Sugino, Hiroshi; Kono, Mihoko; Oka, Toru; Sueta, Daisuke; Komuro, Issei; Tsujita, Kenichi; on behalf of J-Khorana Registry Investigators (TH Open, 2024)
Background Although the close relationship between cancer and venous thromboembolism (VTE) has been identified, risk stratification for VTE in Japanese patients with cancer remains unclear.Objectives This study aimed to validate the Khorana VTE risk assessment score (KRS) for VTE diagnosis and establish an optimal predictive model for VTE in Japanese patients with cancer.Methods A total of 7,955 Japanese patients with cancer were subdivided into low- (0), intermediate- (1–2), and high-score (3) groups according to the KRS. Using 37 explanatory variables, a total of 2,833 patients with cancer were divided into derivation and validation cohorts (5:5). A risk model for Japanese participants was developed using the derivation cohort data.Results The prevalence of VTE in low-, intermediate-, and high-score patients was 1.2, 2.5, and 4.3%, respectively. Logistic regression analysis demonstrated that cancer stage (III–IV) and KRS ≥ 2 were independent and significant predictors of VTE onset. The risk model for VTE assigned 1 point to body mass index ≥25 kg/m2 and 2 points each to the prevalence of osteochondral cancer and D-dimer level ≥1.47 µg/mL. The areas under the curve of the risk model were 0.763 and 0.656 in the derivation and validation cohorts, respectively.Conclusion The KRS was useful in Japanese patients, and our new predictive model may be helpful for the diagnosis of VTE in Japanese patients with cancer.
Keywords: venous thromboembolism; cancer; predictive model